Peran Strategi Branding Terhadap Peningkatan Penjualan Produk - Pretty Naomi Sitompul; Fifi Yunita Harahap; Muhammad Denni Saragih (Sekolah Tinggi Ilmu Ekonomi Bina karya, 2025)
Branding strategy is one of the key factors in building a positive image and increasing product competitiveness in the market. This study aims to determine the role of branding strategy in increasing product sales, in terms of brand awareness, consumer trust, and customer loyalty. The research method used is descriptive qualitative with a literature study approach that examines theories and previous research results regarding the influence of branding on consumer behavior. The results of the study show that an effective branding strategy can create a strong brand identity, increase product value perception, and build an emotional connection between consumers and the brand. This has an impact on increasing consumer purchasing interest and repurchase frequency. Thus, it can be concluded that branding strategies play a significant role in driving product sales growth through the creation of a consistent, credible brand image that is relevant to market needs.